Preparation of ZnO flower/reduced graphene oxide composite with enhanced photocatalytic performance under sunlight. Issue 3 (April 2015) - Xu, Shaohua; Fu, Li; Pham, Tien Song Hiep; Yu, Aimin; Han, Fugui; Chen, Long
Abstract: Reduced graphene oxide (RGO) coated ZnO flower was synthesized by a simple one-pot hydrothermal method. The morphology and properties of ZnO/RGO composites were characterized by UV–vis spectroscopy, Raman spectroscopy, SEM, TEM, EDX, XRD, photoluminescence spectroscopy and photocurrent measurement. It was found that the ZnO flowers were effectively covered with RGO sheets and formed a network structure. The photocatalytic activities of the as-prepared composites were investigated by photodegrading methylene blue under both UV light and sunlight. Results show that the ZnO/RGO composites exhibited a remarkably enhanced photocatalytic efficiency compared to pure ZnO flowers. The cause of the enhanced photocatalytic performance could be ascribed to the synergistic effect between ZnO flowers and RGO sheets. Moreover, we found that the content of graphene oxide introduced into composite material was a crucial factor for its improved photocatalytic performance.